Epicutaneous Immunotherapy Compared with Sublingual Immunotherapy in Mice Sensitized to Pollen (Phleum pratense). (2nd February 2012) - Mondoulet, Lucie; Dioszeghy, Vincent; Ligouis, Mélanie; Dhelft, Véronique; Puteaux, Emilie; Dupont, Christophe; Benhamou, Pierre-Henri
Abstract : Background . The aim of this study was to compare the efficacy of epicutaneous immunotherapy (EPIT) to sublingual immunotherapy (SLIT) in a model of mice sensitized to Phleum pratense pollen. Methods . BALB/c mice were sensitized by sub-cutaneous route to pollen protein extract mixed treated for 8 weeks, using sham, EPIT, or SLIT. Measurements involved the serological response and cytokine profile from reactivated splenocytes, plethysmography after aerosol challenge to pollen, cell, and cytokine contents in the bronchoalveolar lavages (BALs). Results . After immunotherapy, sIgE was significantly decreased in the treated groups compared to sham (P < 0.001 ), whereas sIgG2a increased with EPIT and SLIT (P < 0.001 and P < 0.005 versus sham). Reactivated splenocytes secreted higher levels of Th2 cytokines with sham (P < 0.01 ). Penh values were higher in sham than EPIT and SLIT. Eosinophil recruitment in BAL was significantly reduced only by EPIT (P < 0.01 ). Conclusion . In this model of mice sensitized to pollen, EPIT was at least as efficient as SLIT.